Effectiveness of Google Workspace Literacy as an Educational Tool in Grade 12 HUMSS at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Worldwide, people struggle to balance their workloads while implementing new skill sets in less-than-ideal ways. Development services assist educators in incorporating useful tools in education. Google Workspace for Education is a collection of Google tools and services designed to help schools and homeschools collaborate and keep learning secure. Google Workspace for Education provides various options to meet your organization’s needs. The descriptive study describes the current state of the variable: the literacy of Grade 12 HUMSS students in Bestlink Senior High School using Google Workspace as an educational tool. As a result, there are no presumed causes or effects. The study design will be qualitative, employing surveys to collect data using g-forms to verify subjects.  The respondents, according to gender, consist of 26 males, which is 43.3% of the population and 34 females, which is 56.7%, with a total number of 60 respondents. The most frequent age of the respondents is between 18-19 years'' old, which is 70% of the population. The least frequent of the respondents are between the ages 20-21, 10%. Most respondents believe that Google Literacy Workspace can assist them in improving their learning engagement. The most likely recommendation for them to use Google Workspace as an educational tool is to secure their open workspace account by adding passwords and two-factor authentication. Being able to socialize with friends and other people is one of the things we can consider to alleviate our problems.
Keywords: Google Workspace; Educators; Organization; Development; HUMSS; Bestlink